2003
DOI: 10.1074/jbc.c300197200
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-triggered Membrane Fusion Proceeds Independently of Specific Presynaptic Proteins

Abstract: Complexes of specific presynaptic proteins have been hypothesized to drive or catalyze the membrane fusion steps of exocytosis. Here we use a stage-specific preparation to test the roles of SNAREs, synaptotagmin, and SNARE-binding proteins in the mechanism of Ca 2؉ -triggered membrane fusion. Excess exogenous proteins, sufficient to block SNARE interactions, did not inhibit either the Ca 2؉ sensitivity, extent, or kinetics of fusion. In contrast, despite a limited effect on SNARE and synaptotagmin densities, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 43 publications
(65 reference statements)
2
50
0
1
Order By: Relevance
“…CSC and CV preparations CV-PM (cell surface complex; CSC) and CV preparations were isolated from unfertilized sea urchin (Srongylocentrotus purpuratus, Westwind, BC, Canada) eggs as previously described [6][7][8][9][14][15][16]. All treatments and fusion assays were carried out in baseline intracellular medium (BIM; 210 mM potassium glutamate, 500 mM glycine, 10 mM NaCl, 10 mM Pipes, 0.05 mM CaCl 2 , 1 mM MgCl 2 , 1 mM EGTA; pH 6.7; [23]) supplemented with 2.5 mM ATP and protease inhibitors, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CSC and CV preparations CV-PM (cell surface complex; CSC) and CV preparations were isolated from unfertilized sea urchin (Srongylocentrotus purpuratus, Westwind, BC, Canada) eggs as previously described [6][7][8][9][14][15][16]. All treatments and fusion assays were carried out in baseline intracellular medium (BIM; 210 mM potassium glutamate, 500 mM glycine, 10 mM NaCl, 10 mM Pipes, 0.05 mM CaCl 2 , 1 mM MgCl 2 , 1 mM EGTA; pH 6.7; [23]) supplemented with 2.5 mM ATP and protease inhibitors, unless otherwise stated.…”
Section: Methodsmentioning
confidence: 99%
“…Fusion assays Standard end-point and kinetic fusion assays were carried out as previously described [6,7,9,14]. For each experiment (n), all conditions were tested in replicates of three to four.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibition of exocytosis was not reversible with the addition of cytosol. We do not know the identity of the protein(s) that are targets for the thiol-reactive inhibitors that we used but it is unlikely that they are SNARE proteins alone, as previous studies of CV fusion have shown that SNAREs are not essential for fusion, although they might play regulatory functions Coorssen et al, 2003;Szule et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although granuphilin (15,32) and Synt1A (14) knockout cells show a reduced number of docked granules, they do secrete insulin, suggesting that docking is not a prerequisite for fusion, as also suggested in other cell types (37,38). Synt1A-and granuphilin-deficient animals show virtually no first phase of insulin secretion, and almost all fusion events are due to new-comers (14,15).…”
mentioning
confidence: 98%